Effects of an educational intervention on breast self-examination, breast cancer prevention-related knowledge, and healthy lifestyles in scholars from a low-income area in Bogotá, Colombia (2018)
The aim of this study was to evaluate the effects of an educational intervention on breast self-examination, cancer prevention-related knowledge, practices, and behavior change in scholars from a low-income area in Bogota, Colombia. Uncontrolled trial was conducted in 155 scholars. Two educational sessions, 90 min each, were carried out in March 2015 according to the Colombian guidelines for educational communication in the framework of cancer control. All participants completed a self-reported questionnaire at pre- and post-intervention, as well as 1, 3, and 6 months after the intervention. Breast self-examination was practiced by 78.1% of the scholars, and the overall knowledge of breast cancer risk factors was poor. The educational intervention resulted in significant improvements on breast self-examination practice, the knowledge of the technique, and the knowledge of the main risk factors for breast cancer as well as the practice of physical activity and vegetable intake at 6 months follow-up. An educational intervention according to the Colombian guidelines for educational communication in the framework of cancer control improved the practice of breast self-examination, cancer prevention-related knowledge, as well as the practice of physical activity and vegetable consumption in scholars from a low-income area in Bogota, Colombia. Further randomized controlled studies are warranted. © 2016, The Author(s).